2019
DOI: 10.1021/acs.energyfuels.9b01434
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction of Sewage Sludge To Produce Bio-oil in Different Organic Solvents with In Situ Hydrogenation

Abstract: Liquefaction is a new method of producing crude oil from sewage sludge. The effect of in situ hydrogenation on sewage sludge liquefaction characteristics using different solvents was studied in this research. The highest bio-oil yields were 42.3% in ethanol at 360 °C, 43.1% in acetone at 360 °C, and 26.3% in methanol at 280 °C. Esters were the main components of bio-oils in ethanol and methanol, which comprised 43.55% ethyl esters and 61.05% methyl esters, respectively. N components originating from protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Amides (>31%) were found the most abundant in biocrude, as agreed with a previous study about mixed sludge-derived biocrude [55]. The amides were mainly straight aliphatic (e.g., hexadecanamide, octadecanamide, and 9-octadecenamide, (Z)-), which could be formed from the acylation of carboxylic acids with amines or ammonia [16,56] or the aminolysis of esters with amines or ammonia [57]. Some cyclic amides, such as octanoic acid, morpholide, could be generated from the cyclization of alcohols, ammonia, and amino acids [52].…”
Section: Tablesupporting
confidence: 91%
“…Amides (>31%) were found the most abundant in biocrude, as agreed with a previous study about mixed sludge-derived biocrude [55]. The amides were mainly straight aliphatic (e.g., hexadecanamide, octadecanamide, and 9-octadecenamide, (Z)-), which could be formed from the acylation of carboxylic acids with amines or ammonia [16,56] or the aminolysis of esters with amines or ammonia [57]. Some cyclic amides, such as octanoic acid, morpholide, could be generated from the cyclization of alcohols, ammonia, and amino acids [52].…”
Section: Tablesupporting
confidence: 91%
“…The biomass tends to depolymerized to light fragments during the HTL process at higher temperatures, and these fragments will be reorganized to other forms through different reactions such as condensation, polymerization, and cyclization, thus changing the product composition of liquid, solid phase, and gas. Li et al 86 indicated that the oxygen content of the bio-oil decreased as the temperature increased. Xu et al 87 systematically studied the effect on the bio-oil production and the product composition of HTL temperature of sewage sludge.…”
Section: Htl Of Sludgementioning
confidence: 99%
“…In addition, it was also found that the introduction of alcohol solvent could promote the distribution and transformation of HMs to the biochar through a random/ average effect reported by Pan et al 92 Since the bio-oil produced by HTL often has a high content of oxygen, resulting in bio-oil with low HHV, the introduction of organic matters as a solvent can generate hydrogen in situ that can also improve the quality of the bio-oil. Li et al 86 studied the effect of in situ hydrogenation with liquefaction of sewage sludge using several solvents (e.g., MeOH, EtOH, and acetone). Among these solvents, the highest yield of bio-oil achieved 42.3% in EtOH at the temperature of 360 °C.…”
Section: Htl Of Sludgementioning
confidence: 99%
“…The hydrogen resource of the hydrogenation reaction comes from the upgrading solvents. Dehydration can be interpreted as the removal or esterification of hydroxyl groups from phenols and alcohols at a low temperature, thus reducing the amount of O-containing functional groups and making the O/C ratio low . In addition, the long-chain carboxylic acids can crack under high temperature and high pressure conditions, thus leading to decarboxylation .…”
Section: Resultsmentioning
confidence: 99%
“…33 In addition, the long-chain carboxylic acids can crack under high temperature and high pressure conditions, thus leading to decarboxylation. 33 The findings are consistent with the results of elemental analyses in Table 2.…”
Section: Elementalmentioning
confidence: 99%